Hypocrisy and human rights : resisting accountability for mass atrocities - Cronin-Furman, Kate, 1981- (Cornell University Press, 2022)
"While international human rights pressure can measurably impact repressive states' behavior, it almost never elicits compliance. Instead, repressive states engage in "quasi-compliance", a gamble on doing just enough to escape punishment"--